LINEAR ALIPHATIC UNSATURATED POLYESTERS BASED ON CIS -2- BUTENE -1,4-DIOL: SYNTHESIS AND CHARACTERIZATION (Journal of Sciences, Islamic Republic of Iran)
A new homologous series of linear aliphatic polyesters, such as poly (cis-2- butenylene carboxylate)S, PBms (m is the number of methylene groups in the acid component, m=2-8 have been synthesized by direct polyesterification reactions in anisole, as solvent. FT-IR, 400 MHz H- NMR, C-NMR and elemental analysis were used to establish the structure of polyesters. Molecular weight distributions were studied by GPC. The most narrow distributions were found to be for PB2 and PB8, whereas, the average molecular weight for all polyesters, except PB6, was about 3000-400